UPAYA MENINGKATKAN HASIL DAN AKTIVITAS BELAJAR KETERAMPILAN BERMAIN SERULING RECORDER MELALUI MODEL PEMBELAJARAN TUTOR SEBAYA PADA SISWA KELAS IX A SMP NEGERI 2 COMAL - Christiarni, Endang (Universitas Negeri Semarang, 2014)
Status quo shows thatthe skills to play flute recorder for grade IX students are still low. It can be seen from the score of their test results in which only 15 out of 29 students can score >75 (34.09%) with the average score of 68, 00. This is caused by students behavior during the learning process which did not meet teacher’s expectations. The results shows that the learning model of peer tutoring can: 1) Improve students learning activities in playing flute recorder for grade IX A students of ComalJunior High School 2, academic year of 2011/2012. This is proven by the fact that out of 44 students who achieved lower score on pre-cycle activity (mean 2,19) managed to improve by the end of the second cycle (mean= 3,48) and cosidered as having good qualification. 2) Improve students skills of playing flute recorder . This is proven the increase in the percentage of students passing grade from only 29.55% in the pre cycle activityto 79.55% by the end of the second cycle activities.